What drives U.S. corporate private equity? An historical perspective - Duca, John V.; Sanchez-Colburn, Franklin (Journal of Financial Stability, 2025)
This study models the closely held (PE) share of U.S. nonfinancial corporate equity over time. Corporate income tax rates, the Sarbanes-Oxley Act, default risk, and the real medium-run Treasury yield significantly affect the PE share, consistent with other studies which separately analyze these factors. The PE share is negatively related to business loan delinquencies and real medium-term Treasury rates. High interest rates discourage PE funds from using leverage to finance buyouts of public companies and fund distributions of interim cash distributions that enhance the relative liquidity of the closely held firms in PE fund portfolios. Interim cash distributions by PE funds help to avoid the double-taxation of dividends, thus causing the appeal of PE to rise with corporate income tax rates, which increases the PE share. The PE share rose during the Enron scandal and after the Sarbanes-Oxley Act (SOX), which increased the costs of continuing as, or becoming, a publicly traded corporation. The PE share is well explained and tracked by key macroeconomic variables as well as tax and regulatory policies. • We model the private equity (PE) share of US nonfinancial corporate equity over time. • Business loan delinquencies and real medium-term Treasury rates lower the PE share. • Sarbanes-Oxley increased the PE share by raising the costs of being a public firm. • The PE share is well modeled by key macroeconomic, tax, and regulatory variables.